Postoperative Urinary Retention in Total Vaginal and Abdominal Hysterectomy in Benign Gynecological Disorders - Triarani, Hertia; Priyatini, Tyas (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To assess and compare the incidence of urinary retention in patients post‐vaginal and abdominal total hysterectomy for benign gynecological disorders. Method: This is a comparative analytical study with prospective and retrospective cohort design, which was conducted in Dr. Cipto Mangunkusumo Hospital and Persahabatan Hospital from June 2012 to February 2014. Result: We recruited thirty‐eight research subjects who underwent abdominal hysterectomy, and 18 subjects who underwent vaginal hysterectomy. The majority of cases underwent the procedure for abnormal uterine myoma (55.5%) and adenomyosis (28.9%). Incidence of urinary retention post‐hysterectomy was 33.3% for vaginal hysterectomy, and 31.6% for abdominal hysterectomy. The comparison of the incidence of urinary retention showed no difference between vaginal and abdominal hysterectomies (RR=1.056). Conclusion: Vaginal hysterectomy does not increase the incidence of postoperative urinary retention. However, this study suggests the need for further research with a larger sample size, employing prospective cohort design, with preoperative measurement of postvoiding urine volume (PVR). Keywords: abdominal hysterectomy, urinary retention, vaginal hysterectomy